Integration of Islamic Educational Values in the Practice of Hajj Worship (Spiritual Experience of Hajj Trip in 1444h/2023M) - Asrin, Ahmad (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
AbstractThis study aims to explore the integration of Islamic educational values in the practice of the Hajj pilgrimage, focusing on the researcher's own spiritual experience directly in the implementation of the Hajj in 1444H/2023M. This study uses a qualitative approach, with data collection techniques through participatory observation and literature study. The study subjects were Hajj pilgrims from Kloter 1 KNO Embarkation Medan from Mandailing Natal Regency. The results of the survey indicate that Islamic educational values, such as sincere intentions, piety, patience, and Islamic brotherhood, play a vital role and influence on pilgrims during the Hajj pilgrimage. In addition, it was found that implementing the Hajj pilgrimage is a means of education for pilgrims to obtain these educational values to be applied in their post-Hajj life. This is supported by several factors: experienced Hajj guides and a conducive social environment, which contribute to the success of the integration of Islamic educational values in the practice of the Hajj pilgrimage. Overall, this study confirms the importance of Islamic education in preparing Hajj pilgrims to undergo a more meaningful and spiritually conscious pilgrimage. The Hajj pilgrimage is a ritual and a means of education to obtain educational values in life for humans in general. Keywords: Islamic Education; Hajj; Spiritual Experience.